Gemological characteristics of jewelry-ornamental septaria of the Ulyanovsk region - D. A. Petrochenkov (Известия высших учебных заведений: Геология и разведка, 2019)
Septaria of the Ulyanovsk region are high-quality jewelry and ornamental material. Septaria are associated with lower Cretaceous sediments and are located in the coastal cliffs and the beach area of the Volga river. Septaria consist mainly of calcite — 89 wt. %. Aluminosilicates, quartz, pyrite, ferric oxide, organic matter are present in small amounts. In the streaks of calcite the presence of the microinclusions of graphite, gold, layered aluminosilicates, vernadite, magnetite, and bacteria impregnated with iron oxide, has been established by electron microscopic analysis. Calcite streaks of the septaria have a wide range of colors and textures. The color of calcite is influenced by the admixture of Fe and Mn. The contents of radioactive and carcinogenic elements are close to the background.